The effect of intellectual intelligence, emotional intelligence, spiritual intelligence and understanding of the accountant’s code of ethics on the ethical behavior of accounting students - Asep Kurniawan; Ai Nuraisah; Icih (Proceeding of National Conference on Accounting & Finance, 2023)
The various results of previous studies causes this research to be carried out again to obtain empirical evidence. This study aim to examine some variable that influence ethical behavior of accounting students, such as intellectual intelligence, emotional intelligence, spiritual intelligence and understanding of accountants' code of ethics. This study uses quantitative and using questionnaire to collect data. The tests carried out are validation and reliability tests. The data analysis method used is descriptive statistical analysis, classical assumption test, and hypothesis testing. The results show that intellectual intelligence, emotional intelligence, spiritual intelligence, and understanding of the accountant's code of ethics simultaneously influence the ethical behavior of accounting students and partially intellectual intelligence, spiritual intelligence, and understanding of the accountant's code of ethics have a positive effect on the ethical behavior of accounting students. But emotional intelligence has no effect on the ethical behavior of accounting students.